Quality control using the failure mode effect and analysis to reduce defects in PT. NSP - Nova Wisnianingsih; Agus Nurrokhman (LPPMPK- Universitas Muhammadiyah Cileungsi, 2025)
This research is to analyze service quality and customer satisfaction to find out the factors of consumer/customer complaints so that company performance can be improved and improved. This research uses the Servqual method, the company can then find out consumers' perceptions and expectations, while the company's AHP method is able to sort out which criteria are prioritized first to improve service quality so that the hospital becomes better. The results of the research were conducted with a sample of 100 respondents and 20 question items. In calculating the weighted servqual, the priority for improving the quality of service in the Tangiable dimension is the criterion